Predicting shifts in the mean of a multivariate time series process: An application in predicting business failures - Theodossiou, Panayiotis (My University, 1993)
A firm in the early stages of financial distress exhibits characteristics different from those of healthy firms. As the economic condition of a firm worsens, its financial characteristics shift toward those of failed firms. Practitioners in the financial sector have long been interested in the early detection of a firm’s slide toward insolvency. Several models have been developed with this purpose in mind, but these older models are static in nature. Therefore, a need exists for the development of business failure prediction models that assess the financial condition of firms sequentially over time. This article addresses this need by presenting a sequential business failure prediction model.
Keywords: Bankruptcy prediction; Business failure prediction models; Discriminant analysis; Multivariate cumulative sum procedure; Serial correlation; Sequential procedure